Development of the Harmoni Smart Box Learning Media to Enhance Fifth-Grade Students’ Conceptual Understanding of Ecosystems - Anisa Nurul Fiqriyah; Diki Rukmana (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to develop the Harmoni Smart Box Learning Media, an interactive instructional medium that integrates a three-dimensional ecosystem model, ecosystem concept cards, environmental problem cards, and student-centered exploratory activities to support students’ conceptual understanding. The study employed a Research and Development (R&D) approach based on the ADDIE model. Before classroom implementation, the product was validated by experts in science content, instructional media, pedagogy, and research instrument development. A limited field trial using a one-group pretest–posttest design was subsequently conducted with 32 fifth-grade students at SDN Tengah 03 Jakarta. Product feasibility was assessed using expert validation questionnaires, whereas students’ conceptual understanding was measured through pretest and posttest assessments. The expert validation results showed that the developed learning media achieved a very high level of feasibility across all evaluated aspects. Students’ conceptual understanding also improved after using the media, and the Wilcoxon signed-rank test revealed a statistically significant difference between the pretest and posttest scores (p < 0.05). These findings indicate that the Harmoni Smart Box Learning Media is highly feasible for use in elementary science instruction and shows promising potential to support students’ conceptual understanding in a limited classroom setting. Nevertheless, further studies involving larger and more diverse samples, as well as control groups, are required to evaluate its instructional effectiveness more comprehensively.